Unraveling sources of cyanate in the marine environment: insights from cyanate distributions and production during the photochemical degradation of dissolved organic matter - Rui Wang; Jihua Liu; Yongle Xu; Li Liu; Kenneth Mopper (Frontiers in Marine Science, 2024)
Cyanate is a nitrogen and energy source for diverse marine microorganisms, playing important roles in the nitrogen cycle. Despite the extensive research on cyanate utilization, the sources of this nitrogen compound remain largely enigmatic. To unravel the sources of cyanate, distributions and production of cyanate during photochemical degradation of natural dissolved organic matter (DOM) were investigated across various environments, including freshwater, estuarine, coastal areas in Florida, and the continental and slope regions of the North American mid-Atlantic Ocean (NATL). Cyanate production was also examined during the photochemical degradation of exudates from a typical strain of Synechococcus , an important phytoplankton component. To deepen our understanding of the sources and production mechanisms of cyanate, its production was assessed during the photochemical degradation of a natural seawater DOM supplemented with five nitrogen–containing compounds with distinguishing structures and functional groups. Generally, cyanate exhibited higher concentrations in the Florida coastal, estuarine, and freshwater environments than the NATL. However, cyanate distribution did not consistently align with its production rates. Despite significantly low concentrations in the NATL, DOM from this region exhibited cyanate production rates comparable to estuarine and Florida coastal environments. Although relatively high cyanate concentrations were observed in the freshwaters, DOM in this environment exhibited very low cyanate production rates. A highly significant correlation was observed between cyanate and chlorophyll a (Chl a ) concentrations in these areas. Moreover, in most estuarine and NATL stations, cyanate concentration and production rate in the Chl a maximum layer were significantly higher than in other layers. Cyanate was produced during the photochemical degradation of the Synechococcus exudates. The cyanate production was significantly enhanced when the natural seawater DOM was supplemented with GlycylGlycine, 4-(methylamino) benzoic acid, 4-[ethyl(methyl)amino] benzaldehyde or methyl 2-aminobenzoate. Our study implies that photochemical degradation of marine DOM, especially phytoplankton-derived DOM, is a substantial source of cyanate in the ocean. Additionally, cyanate may form during the degradation of peptides and small aromatic compounds in DOM, providing novel insights into the nitrogen cycle.

Measurement of Antioxidant Activity toward Superoxide in Natural Waters - D. Whitney King; Emma Berger; Zachary Helm; Eleanor Irish; Kenneth Mopper (Frontiers in Marine Science, 2016)

Studies on Hydroxyl Radical Formation and Correlated Photoflocculation Process Using Degraded Wood Leachate as a CDOM Source - Luni Sun; Kenneth Mopper (Frontiers in Marine Science, 2016)

Competition between photochemical and biological degradation of dissolved organic matter from the cyanobacteria Microcystis aeruginosa - Thais B. Bittar; Armando A. H. Vieira; Aron Stubbins; Kenneth Mopper (Limnology and Oceanography, 2015)
Extracellular and intracellular dissolved organic matter (E‐DOM and I‐DOM, respectively) produced in axenic cultures by the cosmopolitan cyanobacteria Microcystis aeruginosa were characterized, and photoreactivity, bioreactivity, and the effects of phototransformations on bioavailability of E‐DOM and I‐DOM were assessed in laboratory experiments. Chromophoric (CDOM) and fluorescent (FDOM) properties were analyzed by spectrophotometry, and chemical signatures were obtained by ultrahigh resolution Fourier transform ion cyclotron resonance mass spectrometry (FTICR‐MS). E‐DOM was more heterogeneous regarding optical characteristics as indicated by the presence of multiple CDOM peaks and the more even distribution of FDOM components, and had less absolute and relative numbers for molecular formulae containing nitrogen (N) than I‐DOM. E‐DOM was more photolabile, with greater photochemical removal of dissolved organic carbon (DOC), CDOM and FDOM, and exhibited more pronounced photochemical alterations in molecular formulae composition than I‐DOM. E‐DOM was less biolabile, with less biological removal of DOC, CDOM, and protein‐like fluorescent material, and supported lower rates of bacterial productivity than I‐DOM. Phototransformations reduced the bioavailability of E‐DOM and I‐DOM, as shown by lower bacterial productivity and longer DOC and CDOM half‐lives in bioassays with photoirradiated DOM in comparison to those with nonirradiated DOM. Analyses of CDOM, FDOM, and FTICR‐MS revealed that the decrease in bioavailability was caused primarily by photolysis of the biolabile DOM, indicating competition between photochemical and biological removal of cyanobacterial DOM. These results provided insights into mechanistic effects of independent and combined photochemical and biological degradation on M. aeruginosa ‐derived DOM.

Loss of optical and molecular indicators of terrigenous dissolved organic matter during long-term photobleaching - John R. Helms; Jingdong Mao; Aron Stubbins; Klaus Schmidt-Rohr; Robert G. M. Spencer; Peter J. Hernes; Kenneth Mopper (Aquatic Sciences, 2014)

Illuminated darkness: Molecular signatures of Congo River dissolved organic matter and its photochemical alteration as revealed by ultrahigh precision mass spectrometry - Aron Stubbins; Robert G. M. Spencer; Hongmei Chen; Patrick G. Hatcher; Kenneth Mopper; Peter J. Hernes; Vincent L. Mwamba; Arthur M. Mangangu; Jose N. Wabakanghanzi; Johan Six (Limnology and Oceanography, 2010)
Congo River water was filtered and then irradiated for 57 d in a solar simulator, resulting in extensive photodegradation of dissolved organic matter (DOM). Whole‐water (i.e., unfractionated) DOM was analyzed pre‐ and post‐irradiation using ultrahigh resolution Fourier transform ion cyclotron mass spectrometry (FT‐ICR MS), revealing the following three pools of DOM classified based upon their photoreactivity: (1) photo‐resistant, (2) photo‐labile, and (3) photo‐produced. Photo‐resistant DOM was heterogeneous, with most molecular classes represented, although only a small number of aromatics and no condensed aromatics were identified. The photoproduced pool was dominated by aliphatic compounds, although it included a small number of aromatics, including condensed aromatics. Aromatic compounds were the most photoreactive, with > 90% being lost upon irradiation. Photochemistry also resulted in a significant drop in the number of molecules identified and a decrease in their structural diversity. The FT‐ICR MS signatures of two classes of refractory organic matter, black carbon and carboxylic‐rich alicyclic molecules (CRAM), were present in the sample prior to irradiation, indicating that the Congo River could be a significant exporter of recalcitrant DOM to the ocean. All black carbon‐like molecules identified in the initial sample were lost during irradiation. Molecular signatures consistent with CRAM were also highly photo‐labile, demonstrating that environmental solar irradiation levels are capable of removing these refractory compounds from aquatic systems. Irradiation also shifted the molecular signature of terrestrial DOM toward that of marine DOM, thereby complicating the task of tracking terrestrial DOM in the ocean.

Absorption spectral slopes and slope ratios as indicators of molecular weight, source, and photobleaching of chromophoric dissolved organic matter - John R. Helms; Aron Stubbins; Jason D. Ritchie; Elizabeth C. Minor; David J. Kieber; Kenneth Mopper (Limnology and Oceanography, 2008)
A new approach for parameterizing dissolved organic matter (DOM) ultraviolet‐visible absorption spectra is presented. Two distinct spectral slope regions (275‐295 nm and 350‐400 nm) within log‐transformed absorption spectra were used to compare DOM from contrasting water types, ranging from wetlands (Great Dismal Swamp and Suwannee River) to photobleached oceanic water (Atlantic Ocean). On the basis of DOM size‐fractionation studies (ultrafiltration and gel filtration chromatography), the slope of the 275‐295‐nm region and the ratio of these slopes ( S R ; 275‐295‐nm slope : 350‐400‐nm slope) were related to DOM molecular weight (MW) and to photochemically induced shifts in MW. Dark aerobic microbial alteration of chromophoric DOM (CDOM) resulted in spectral slope changes opposite of those caused by photochemistry. Along an axial transect in the Delaware Estuary, large variations in S R were measured, probably due to mixing, photodegradation, and microbial alteration of CDOM as terrestrially derived DOM transited through the estuary. Further, S R varied by over a factor of 13 between DOM‐rich wetland waters and Sargasso Sea surface waters. Currently, there is no consensus on a wavelength range for log‐transformed absorption spectra. We propose that the 275‐295‐nm slope be routinely reported in future DOM studies, as it can be measured with high precision, it facilitates comparison among dissimilar water types including CDOM‐rich wetland and CDOM‐poor marine waters, and it appears to be a good proxy for DOM MW.

Evaluating the photoalteration of estuarine dissolved organic matter using direct temperature-resolved mass spectrometry and UV-visible spectroscopy - Elizabeth C. Minor; Brent J. Dalzell; Aron Stubbins; Kenneth Mopper (Aquatic Sciences, 2007)

Determination of the Tropospheric Hydroxyl Radical by Liquidphase Scrubbing and HPLC: Preliminary Results - Xiaohui Chen; Kenneth Mopper (Journal of Atmospheric Chemistry, 2000)

The role of surface‐active carbohydrates in the formation of transparent exopolymer particles by bubble adsorption of seawater - Jian Zhou; Kenneth Mopper; Uta Passow (Limnology and Oceanography, 1998)
Experiments were performed to examine the role of surface‐active polysaccharides in the formation of transparent exopolymer particles (TEP) by bubble adsorption in seawater. Filtered (1.0 µm, 0.45 µm) and ultrafiltered (0.1 µm, 100 kDa, and 10 kDa) seawater samples were bubbled in a glass foam tower. The neutral sugar composition, concentration of TEP, and concentration of surface‐active carbohydrates in generated foam samples were determined. Three different surface seawater samples (Monterey Bay, California; Shannon Point, Anacortes, Washington; and East Sound, Orcas Island, Washington) were used in the experiments. Significant concentrations of pre‐existing and new TEP were extracted into foam by bubble adsorption. Newly generated TEP accounted for 28–52% of the TEP collected in the foam samples by bubbling 1.0‐µm‐filtered samples. Neutral sugar composition analyses of foam samples derived as a function of bubbling time indicated that two types of surface‐active carbohydrates were extracted by bubble adsorption: highly surface‐active carbohydrates, which were extracted initially, and less surfaceactive carbohydrates. As in our previous mesocosm study (Mopper et al. 1995), highly surface‐active polysaccharides were enriched in deoxysugars (fucose and rhamnose), whereas the less surface‐active polysaccharides and residual (bubble‐stripped) water were glucose rich. In addition, the highly surface‐active fraction was strongly enriched in covalently bound sulfate. The concentrations of TEP and surface‐active carbohydrates that were extracted into the foam both decreased sharply with decreasing filter size used to filter samples prior to bubbling, in agreement with theoretical considerations. The results of this study suggest that bubble adsorption of sulfate‐rich surface‐active carbohydrates is an important pathway for the formation of TEP in surface waters, especially during algal blooms.

Free‐floating drifter for photochemical studies in the water column - David J. Kieber; Brian H. Yocis; Kenneth Mopper (Limnology and Oceanography, 1997)
A free‐floating drifter was designed to directly determine in situ photochemical production rates, photolysis rates, and light fluxes in seawater. This drifter consisted of six trays that were suspended in series from a single buoy line. The trays were constructed so that the attached quartz vessels, containing filtered seawater, were exposed to both downwelling and upwelling irradiation. The quartz vessels were sealed at both ends with ribbed TFE Teflon stoppers that permitted multiple subsampling without introduction of a headspace. The free‐floating drifter was used to study photochemical processes in antarctic waters. It performed well during 12–15‐h deployments, even in rough seas with sustained winds between 15 and 26 m s −1 . Although not tested here, the drifter should perform equally well in the study of photochemical processes in freshwater environments.